The power of trees : how ancient forests can save us if we let them - Wohlleben, Peter, 1964- (David Suzuki Institute : Greystone Books, 2023)
"From the international bestselling author of The Hidden Life of Trees. An illuminating manifesto on ancient forests: how they adapt to climate change by passing their wisdom through generations, and why our future lies in protecting them. In his beloved book The Hidden Life of Trees, Peter Wohlleben revealed astonishing discoveries about the social networks of trees and how they communicate. Now, in The Power of Trees, he turns to their future, with a searing critique of forestry management, tree planting, and the exploitation of old growth forests. As human-caused climate change devastates the planet, forests play a critical role in keeping it habitable. While politicians and business leaders would have us believe that cutting down forests can be offset by mass tree planting, Wohlleben offers a warning: many tree planting campaigns lead to ecological disaster. Not only are these trees more susceptible to disease, flooding, fires, and landslides, we need to understand that forests are more than simply a collection of trees. Instead, they are ecosystems that consist of thousands of species, from animals to fungi and bacteria. The way to save trees, and ourselves? Step aside and let forests--which are naturally better equipped to face environmental challenges--heal themselves. With the warmth and wonder familiar to readers from his previous books, Wohlleben also shares emerging scientific research about how forests shape climates both locally and across continents; that trees adapt to changing environmental conditions through passing knowledge down to their offspring; and how old growth may in fact have the most survival strategies for climate change. At the heart of The Power of Trees lies Wohlleben's passionate plea: that our survival is dependent on trusting ancient forests, and allowing them to thrive."--